Perinatal outcome of preterm labour with and without prelabour rupture of membranes - an observational study - Keya Chatterjee; Aloke Kumar De; Aparna Chakraborty (Barpeta Obstetrics and Gynaecological Society, 2021)
Objective - This study was done with the mindset to identify preventable risk factor for preterm labor and develop optimum management protocol to achieve, lesser maternal and perinatal morbidity and mortality by observing mother with preterm labour. Method - In this study 100 antenatal women admitted with preterm labour with gestational age more than 28 completed weeks to less than 37 completed weeks were observed till delivery. Maternal and fetal outcome were analyzed and measures that could reduce perinatal morbidity and mortality were identified. Results - All the women with preterm labour had presented with PROM too. Maternal outcome, perinatal morbidity and mortality all showed close relation with the duration of rupture of membranes, with 39.28% of mother with more than 36 hours since rupture of membranes had greater perinatal morbidity. Those babies with gestational age between 28-32 weeks had perinatal morbidity in 51.43% cases and mortality was 34.29%. Subclinical urogenital infection was present in most of the mothers with 12% of them having febrile morbidity. Cervical swab was positive in 23% of the cases with 10 cases of normal vaginal flora and 4 cases of E. coli. Hyperbilirubinemia and RDS both having incidence of 29.60% followed by sepsis with incidence of 14% were responsible for most of the perinatal morbidity and mortality. Conclusion - A gestational age approach to therapy is found important. Perinatal mortality and morbidity was not influenced by the mode of delivery. As the duration of PPROM increased, perinatal morbidity and mortality also increased.